FACTORS PRODUCTIVITY IN SMALL SCALE UPLAND VEGETABLE PRODUCTION IN THE SOUTH – SOUTH REGION OF NIGERIA - Sunday Brownson AKPAN; Monday IDIONG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study examined the social and economic characteristics of fluted pumpkin farmers and determined the extent of farm resource productivity. The study was carried out in the southern region of Nigeria. 100 leafy fluted pumpkin farmers were used in the study. Results showed that majority of the farmers (72.00%) were females, 74.00% were married, the mean age and farming experience stood at 42.97 and 14.96 years respectively. Social capital formation was very poor, while the mean household size and farm income were 6.00 members and N188, 560.00 respectively. The empirical result showed that; family labour, hired labour, quantity of seed, manure, fertilizer and farm size were significant farm inputs that influenced the production of fluted pumpkin. Apart from fertilizer utilization which occurs in irrational stage in a classical production surface, all other farm inputs’ levels of utilization were in the rational stage. The study also found increasing rate of return (1.7847) among fluted pumpkin farms in the region. In addition, more family labour was substituting hired labour while more manure was substituting fertilizer usage in fluted pumpkin production in the region. The study recommends fertilizer subsidy and timely delivery to vegetable farmers in the rural areas of the State.